Die Novellierung des japanischen IPR – Eine kurze Einführung zum neuen Rechtsanwendungsgesetz - Sakurada, Yoshiaki; Nishitani, Yuko; Schwittek, Eva (Zeitschrift für Japanisches Recht, 2006)
One of the most recent law reforms in Japan concerns the Act on the Application of Laws. On 15 June 2006, the Japanese Parliament passed the Hô no tekiyô ni kan suru tsûsoku-hô, a revised and renamed version of the Hôrei that dates from 1898. The new law will come into effect as of 1 January 2007. This article gives a short overview of the legislative process and the changes of the law, followed by a German translation of the law. In sessions dating from May 2003 to July 2005, the Subcommittee for the Modernization of the Act on the Application of Laws (part of the Legislative Commission of the Ministry of Justice) worked out fundamental innovations that were approved by the Legislative Commission of the Ministry of Justice on 6 September 2005. Based on this report, the Ministry of Justice, in cooperation with the Legislative Department of the Cabinet, drafted a bill that passed the Upper House on 19 April 2006, and the House of Representatives on 15 June 2006. The reform covers the whole law except for the provisions regarding the international family and inheritance law, which were already amended in 1989. The main focus of the present amendment lies on the provisions concerning the international contract law (Articles 7–12) and the international law of torts (Articles 17–22). Also, the text was changed from katakana to hiragana. This and the new naming of the law constitute measures of modernization aimed at giving people easier access to the law.